Capacity Efficiency Improvment And Innovation Technology Transfer Of Dairy Cow Feed Processing At Dairy Cow Farm Center, Brau Village, Batu City - Evi Kurniati (Journal of Innovation and Applied Technology, 2015)
Batu City has a potential livestock (rabbits, beef cattle, and dairy cows). Brau  Village in Batu City is one of the centers of dairy cow farmers and they are the member of business cooperative "Margo Makmur Mandiri" which is a partner with KUD "DAU". The need of concentrate for feed is 60% in addition to elephant grass. Purchasing price of animal feed in KUD "DAU" is Rp.85.000, - per zak @ 50 kg while the animal feed from KSU Rp.75.000/zak with profits 12,000, - up to 20,000/zak. The number of dairy cows in the Brau Village is 500 cows with the need of 6 kg per cow per day.  Therefore at least it is needed 18 tons for 10 days feeding.  Especially during the dry season, the demand is 20-25 tons per 10 days. Technology transfer is required for improving capacity and efficiency of feed production including grinders (cap crusher/hammer mill), genset power plants, conveyor, cyclone and blower. The coaching was pursued about quality standards, marketing and commercial business management. This program can improve the quality, quantity and profits that impact on the welfare of society, especially cow dairy farmers in Brau Village. Keywords:  capacity, efficiency, feed, dairy cow, technology dissemination